2017
DOI: 10.1002/cne.24343
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory neuron‐specific Cre‐dependent red fluorescent labeling using VGAT BAC‐based transgenic mouse lines with identified transgene integration sites

Abstract: Inhibitory neurons are crucial for shaping and regulating the dynamics of the entire network, and disturbances in these neurons contribute to brain disorders. Despite the recent progress in genetic labeling techniques, the heterogeneity of inhibitory neurons requires the development of highly characterized tools that allow accurate, convenient, and versatile visualization of inhibitory neurons in the mouse brain. Here, we report a novel genetic technique to visualize the vast majority and/or sparse subsets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
(104 reference statements)
2
11
0
Order By: Relevance
“…In fact, the absence of GABAergic somas has been used to delineate the boundaries of the VMH (Jarvie & Hentges, 2012). Taking advantage of mice expressing the fluorescent reporter tdTomato under the promoter of the vesicular transporter of GABA (VGat-tdTomato) (Kaneko et al, 2018) we observed, as expected, lower signal intensity inside the boundaries of the VMH (Fig. 6A) that was consistent across the AP regions of the VMH.…”
Section: Resultssupporting
confidence: 79%
“…In fact, the absence of GABAergic somas has been used to delineate the boundaries of the VMH (Jarvie & Hentges, 2012). Taking advantage of mice expressing the fluorescent reporter tdTomato under the promoter of the vesicular transporter of GABA (VGat-tdTomato) (Kaneko et al, 2018) we observed, as expected, lower signal intensity inside the boundaries of the VMH (Fig. 6A) that was consistent across the AP regions of the VMH.…”
Section: Resultssupporting
confidence: 79%
“…Wild-type and VGAT-tdTomato mice from C57BL/6 backgrounds [18] were used in this study. All procedures for the care and treatment of animals were performed according to the Japanese Act on the Welfare and Management of Animals and the Guidelines for Proper Conduct of Animal Experiments issued by the Science Council of Japan.…”
Section: Animalsmentioning
confidence: 99%
“…2a). Because the VGAT-tdTomato mice expressed tdTomato specifically in inhibitory interneurons throughout the central nervous system (CNS) [18], we determined whether the transduced (GFP-expressing) cells were inhibitory GABAergic neurons without immunohistochemistry. The mice were sacrificed 3 weeks after viral injection.…”
Section: Efficient Transduction Throughout the Brain After Intravenoumentioning
confidence: 99%
“…Wild-type and VGAT-tdTomato mice of C57BL/6 backgrounds [18] were used in this study. All procedures for the care and treatment of animals were performed according to the Japanese Act on the Welfare and…”
Section: Animalsmentioning
confidence: 99%
“…To examine whether the mGAD65 promoter works exclusively in inhibitory neurons, we injected VGAT-tdTomato mice with AAV-PHP.B-expressing GFP under the control of the mGAD65 promoter or mDlx enhancer (100 µL, 5.0 × 10 13 viral genome/ml) intravenously, which expressed tdTomato speci cally in inhibitory interneurons throughout the central nervous system (CNS) [18] ( Fig. 2A).…”
Section: E Cient Transduction Throughout the Brain After Intravenous mentioning
confidence: 99%